Ego State Therapy: A Randomized Controlled Trial on Prosocial and Health Motivational Outcomes in Young Adults with Physical Disabilities - Malik, Shazia (Psychological Research in Individuals with Exceptional Needs, 2024)
This study aimed to evaluate the effectiveness of Ego State Therapy (EST) in enhancing prosocial behavior and health motivation among young adults with mild physical disabilities. A randomized controlled trial (RCT) design was employed, involving 30 participants aged 18-30 with diagnosed mild physical disabilities. Participants were randomly assigned to either the intervention group (n=15), which received eight 90-minute sessions of EST, or the control group (n=15), which received no intervention. Prosocial behavior and health motivation were assessed using the Prosocialness Scale for Adults (PSA) and the Health Motivation Scale (HMS), respectively, at baseline, post-intervention, and five-month follow-up. Data were analyzed using SPSS-27 software, with analysis of variance (ANOVA) for repeated measurements and Bonferroni post-hoc tests to control for multiple comparisons. Results indicated significant improvements in prosocial behavior (F(2, 28) = 12.45, p < 0.001) and health motivation (F(2, 28) = 10.89, p < 0.001) in the intervention group compared to the control group. These improvements were sustained over the five-month follow-up period, with significant interaction effects between group and time for both prosocial behavior (F(2, 28) = 8.67, p < 0.001) and health motivation (F(2, 28) = 9.23, p < 0.001). Bonferroni post-hoc tests confirmed significant improvements from baseline to post-intervention and from baseline to follow-up in the intervention group, with no significant changes in the control group. Ego State Therapy significantly enhances prosocial behavior and health motivation in young adults with mild physical disabilities, with sustained effects over a five-month follow-up period. These findings suggest that EST is a valuable therapeutic approach for promoting psychological integration and well-being in this population. Future research should explore the mechanisms underlying these effects and the potential benefits of integrating EST with other therapeutic modalities.